ANALISIS PENGARUH MOMENTUM, TRADING VOLUME DAN SIZE TERHADAP DISPOSITION EFFECT DAN RETURN APLIKASI CROSS SECTIONAL REGRESSION (Studi pada Indeks Saham Kompas 100 Tahun 2012-2015) - Maharani, Ema; Arfianto, Erman Denny (Faculty of Economics and Business Diponegoro University, 2017)
Momentum and disposition effect in modern stock markets are distractions against the Efficient Market Hypothesis. The effect might be elaborated by disposition effect model in which momentum is explored through behavioral bias. The aim of this research was to analyze the propensity of previously winning-stock to perform better than losing-stock as a strategy of momentum attributable to disposition effect. The study case incorporated Stock Index of Kompas 100 in Indonesia Stock Exchange during the period of 2012â€“2015 by employing cross sectional regression.Weekly stock data from 79 companies were taken as sample–comprising of volume and outstanding share. The variables consist of momentum in the sort-term, medium-term, and long term; consecutively taken from past-return week-1, past-return week 5 to 52, past return week 52 to 156. Additionally, to examine the size, trading volume variables were used consisting of average trading volume in the sort-term, medium-term, and long term; consecutively taken from week 1 to 4, 5 to 52, and 53 to 156.Capital gains overhang were used as a proxy of disposition effect. The results revealed that momentum exists on Indonesia Stock Exchange; furthermore, capital gains overhang is sufficient to be a proxy of disposition effect. In other words, disposition effect is driven by momentum. Up to the point od this study, Indeks Stock Kompas 100 has experienced a capital losses; implicating an inclination to remain perform satisfactorily ahead.